Understanding Patients’ Perspectives on Opt-Out, Incentivized, and Mandatory HIV Testing - Noland, Carey M; Vaughn, Nicole A; Sun, Sirena; Schlecht, Hans P (International Journal of Health Sciences, 2015)
Background: Currently, widespread HIV testing is the best preventive action against further spread of the HIV epidemic. However, over 40% of the U.S. population has never been tested for HIV and 25% of those with HIV have never been tested. To increase testing rates, in 2006 the CDC advised healthcare settings to conduct testing on an opt-out basis. Methods: Qualitative, semi-structured interviews with ten seropositive patients and ten seronegative were conducted to address the lack of studies investigating patientsâ€™ acceptance of and attitude towards this and more novel testing models, e.g. incentivized or anonymous mandatory testing. Participants were asked about their HIV testing history and attitudes towards opt-out, incentivized, and mandatory anonymous HIV testing. Results: Major themes were identified using grounded theory data analysis. All participants were receptive to opt-out testing, and saw the removal of separate written consent as beneficial as long as patients were given the opportunity to consent in some form. Conclusion: Ultimately, both mandatory and opt-out testing were equally indicated by participants as being the most effective testing model at increasing testing rates. A firm understanding of patientsâ€™ perspectives allows for development of effective HIV testing initiatives that are patient-sensitive and can substantially reduce HIV infection rates. Keywords: HIV testing, opt-out HIV testing, incentivized HIV testing, mandatory HIV testing, patient education. Â